Analisis Kebijakan Dividen Dan Nilai Perusahaan Terhadap Harga Saham Pada PT AKR Corporindo Tbk Tahun 2015-2024 - Nur Khomsatun Janah; Iriana Kusuma Dewi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze of dividend policy and firm value on stock prices of PT AKR Corporindo Tbk listed on the Indonesia Stock Exchange during the 2015–2024 period. Dividend policy is proxied by the Dividend Payout Ratio (DPR), while firm value is proxied by the Price to Book Value (PBV). This research employs a quantitative approach using secondary data obtained from annual financial statements and year-end closing stock prices. The analytical technique applied is descriptive quantitative analysis through the calculation of financial ratios and observation of inter-variable relationship patterns. The results indicate that the average DPR of PT AKR Corporindo Tbk is 62.39%, reflecting a relatively high dividend policy, while the average PBV of 2.143 indicates that the firm value is in the fair category. Movements in DPR and PBV tend to be aligned with stock price fluctuations, although deviations occur in certain periods due to internal and external factors. Overall, dividend policy and firm value play an important role in influencing the company’s stock price movements